The Impact of Inclusive Leadership and Psychological Capital on Women’s Employee Performance: The Mediating Role of Job Crafting in Islamic Organizations - Azwad Rizal; Djoko Soelistya (WISE Pendidikan Indonesia, 2026)
This study examines the impact of inclusive leadership and psychological capital on women's employee performance, with a focus on the mediating role of job crafting. Using a quantitative approach, data were collected from 100 employees at the Baitul Maghfiroh Cooperative, an organization operating under Islamic leadership values. The analysis, conducted using Structural Equation Modeling (SEM), revealed that inclusive leadership positively influences women’s performance, with a stronger effect observed for women employees compared to their male counterparts. Psychological capital was found to enhance women's performance by fostering resilience and optimism. Furthermore, job crafting was identified as a significant mediator between inclusive leadership and employee performance. These findings highlight the importance of fostering inclusive leadership and psychological capital in creating supportive work environments for women employees, ultimately improving their performance and career progression. The contribution of this research lies in providing valuable insights into gender-responsive leadership practices within the context of Islamic organizations, offering practical recommendations for improving women's performance and empowerment in the workplace.